The National Institutes of Health StrokeNet Training Core - Vahidy, Farhaan S. (Stroke, 2019)
BACKGROUND AND PURPOSE: The National Institutes of Health (NIH) StrokeNet provides a nationwide infrastructure to advance stroke research. Capitalizing on this unique opportunity, the NIH StrokeNet Training Core (NSTC) was established with the overarching goal of enhancing the professional development of a diverse spectrum of professionals who are embedded in the stroke clinical trials network of the NIH StrokeNet. METHODS: This special report provides a descriptive account of the rationale, organization and activities of the NSTC since its inception in 2013. Current processes and their evolution over time for facilitating training of NIH StrokeNet trainees have been highlighted. Data collected for monitoring training are summarized. Outcomes data (publications and grants) collected by NSTC was supplemented by publicly available resources. RESULTS: The NSTC comprises of cross-network faculty, trainees and education coordinators. It helps in development and monitoring of training programs and organizes educational and career development activities. Trainees are provided directed guidance towards their mandated research projects, including opportunities to present at the International Stroke Conference. The committee has focused on developing sustainable models of peer-to-peer interaction and cross-institutional mentorships. A total of 124 professionals (43.7% female, 10.5% underrepresented minorities) have completed training between 2013 and 2018, of whom 55% were clinical vascular neurologists. Of the total, 85% transitioned to a formal academic position and 95% were involved in stroke research post-training. Altogether, 1,659 indexed publications have been authored or co-authored by NIH StrokeNet Trainees, of which 58% were published during or after their training years. Based on data from 109 trainees, 33% had submitted 72 grant proposals as principal or co-principal investigators of which 22.2% proposals have been funded. CONCLUSION: NSTC has provided a foundation to foster nationwide training in stroke research. Our data demonstrate strong contribution of trainees towards academic scholarship. Continued innovation in educational methodologies is required to adapt to unique training opportunities such as the NIH StrokeNet.